Cellular neurothekeoma: case report and its (un) relation with nerve sheath myxoma - Cristián Navarrete-Dechent; Maximiliano Curi-Tuma; Celeste Marín; Sergio González; Mauricio Sandoval-Osses (Sociedade Brasileira de Dermatologia, 2015)
Abstract Neurothekeoma is an uncommon, benign neoplasm presenting in young adults, primarily on the head and neck. It was initially related to nerve sheath myxoma but with the advent of immunohistochemistry, new insights into its cellular differentiation and origin have emerged, unlinking Neurothekeoma and nerve sheath myxoma. Herein we describe a 19-year-old male who had had a frontal, fl esh-colored, asymptomatic papule for 2 years. Histology showed a dermal fusocellular-spindle cell tumor, including an eosinophilic cytoplasm with mild cellular pleomorphism and moderately dense fi brous stroma. IHQ was positive for CD10 and negative for S100 and Claudin-1. These fi ndings were compatible with cellular Neurothekeoma. The lesion was completely extirpated and at the 6-month follow-up, the patient was asymptomatic and had experienced no recurrences.